Digital Transformation and Sustainable Business Strategy in Sharia Umrah Travel: Implications for the Muslim Community Economy - Dida Novandika; Muhamad Zen; Fatmawati Fatmawati (Islam and Social Sciences Review, 2025)
This study aims to analyze the sustainable business model of Sharia Umrah travel and its contribution to the Muslim community economy in the era of digital service transformation. The research employs a qualitative approach using the Systematic Literature Review (SLR) method by examining reputable scientific articles indexed in Scopus, Web of Science, and ScienceDirect databases. The findings reveal that the integration of sustainable strategy, business model innovation, and digital transformation contributes significantly to the development of sustainable business practices through the synergy of economic, social, and environmental dimensions. Digitalization functions as a strategic enabler that enhances operational efficiency, service transparency, and the overall experience of Umrah pilgrims. Furthermore, Sharia Umrah travel contributes to the Muslim community economy through job creation, the expansion of Islamic financial inclusion, and the strengthening of the halal ecosystem. However, the implementation of sustainable business models still faces challenges related to technological adoption gaps and the lack of comprehensive strategic integration. The originality of this study lies in the development of an integrative conceptual framework that combines sustainable strategy, business model innovation, digital transformation, and maqashid shariah within a holistic perspective, which remains underexplored in previous studies. Theoretically, this study contributes to the advancement of sustainable strategy literature within the context of Islamic economics. Practically, it provides strategic insights for industry practitioners in designing adaptive, sustainable, and welfare-oriented Sharia Umrah travel business models. Keywords: Sustainable strategy, Digital transformation, Business model innovation, Sharia Umrah travel, Muslim community economy.